Republic of Belarus : 2012 Article IV Consultation and Second Post-Program Monitoring Discussions: Staff Report; Informational Annex; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper focuses on the 2012 Article IV Consultation and Second Post-Program Monitoring Discussions with Belarus. Since mid-2011, the authorities have been implementing stabilization measures. The financial system has weathered the 2011 crisis, and banks' capital has been replenished with general budget resources. Executive Directors have welcomed the Belarusian economy's emergence from the 2011 crisis owing to the authorities' commendable adjustment policies in the second half of the year. Directors have also stressed the importance of ensuring consistency among the authorities' policy goals.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet